Agricultural Syndicates in France - Wolff, Henry W.; A., W. J. (Quarterly Journal of Economics, 1893)
Journal Article Agricultural Syndicates in France Get access Henry W. Wolff Henry W. Wolff Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 8, Issue 1, October 1893, Pages 98–102, https://doi.org/10.2307/1882880 Published: 01 October 1893